Exporting autocracy: how China's extra-jurisdictional autocratic influence caused democratic backsliding in Hong Kong. Issue 1 (2nd January 2021) - Fong, Brian C. H.
ABSTRACT: In the global trend of democratic backsliding, Hong Kong provides an illustrative case of how democratic institutions could be degenerated by "exporting autocracy". After 1997, Hong Kong's semi-democracy has come under continuous pressure by China's extra-jurisdictional autocratic influence. When about two decades of exporting autocracy has almost made Hong Kong a semi-democratic façade, China imposed the National Security Law in June 2020 placing the last straw that breaks its semi-democracy. The case study of Hong Kong offers comparative observations about China's exporting autocracy across its surrounding jurisdictions in the Asia-Pacific region.